Electronic and optical properties of MX3 (M = Ti, Zr and Hf; X = S, Se) structures: A first principles insight. Issue 5 (5th January 2016) - Abdulsalam, Mahmud; Joubert, Daniel P.
Abstract : Abstractauthoren Abstractauthoren The electronic and optical properties of semiconducting TiS3, HfS3, HfSe3, ZrS3, and ZrSe3 with structure P21 /m have been investigated for the first time at the G 0 W 0 and BSE level of approximations, respectively. The structures were relaxed using PBE with the inclusion of van der Waal's correction terms to account for long‐range dispersion forces, which is a necessary ingredient in predicting an accurate description of structural properties of layered systems. In order to predict reasonable estimates of the electronic properties, MBJ, HSE06, and G 0 W 0 were used to calculate the fundamental band gaps of the structures and the Bethe–Salpeter equation (BSE) was solved to obtain an accurate description of the optical properties of the compounds. It is found that the compounds have G 0 W 0 band gaps between 0.58 to 2.17 eV. Their optical absorption spectra revealed that they start to absorb light in the range of 0.9–1.63 eV making them potential materials for third‐generation solar photovoltaic applications and possible photo‐catalysis applications.